The regional dimension of agricultural land development in Poland in pre- and post-accession periods - Dzun, Włodzimierz; Musiał, Wiesław (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
The paper discusses the problems of agricultural land use changes in Poland in the period between 1990–2012. Research shows large differences between the dynamics of the loss of these resources and the dynamics of their loss on agricultural holdings. In this period the area under agricultural production decreased by 0.7 million hectares, while the area in use as farms fell by about 3.2 million ha. At the same time showed farms strong growth in their area of agricultural land, which had little or no agricultural activity. Progressing at a pace is the process taking agricultural land out of production. With Polish agriculture under the CAP of the EU, and due, in particular, to the introduction of area payments, the process had slowed down significantly. However, with a lack of improvement in the profitability of agricultural production and increasing income opportunities outside of agriculture the process in recent years has clearly been revived. The scale and dynamics of these processes is strongly regionally differentiated. Research indicates that the smallest decline in area of agricultural land resource and the smallest scale not using these resources are attributed to Provinces with a favourable agrarian infrastructure and good agricultural practices, for example in the Provinces of Kujawy Pomosrskie (Pomerania), Greater Poland, Opole, and Podlaskie. At the other extreme, there are the Province with large agrarian fragmentation, i.e. Podkarpackie, Małopolska, Swietokrzyskie and Silesia. The scale of the process clearly inhibits opportunities for improvement of the agrarian structure and indicates a lack of instruments in agricultural policy to limit this.
Keywords: economy of agricultural land; agrarian changes